Profitability of Mergers and Acquisitions in Finland before and during the Financial Crisis - Nieminen, Joni (My University, 2015)
This research thesis concentrates on evaluating the short- and long-term profitability of Finnish companies M&A transactions. Examined full sample period includes the years from 2001 to 2010. Total period is also divided into two sub-periods in order to analyze the recent Financial Crisis’ impact on the profitability of M&A transactions. General statement from previous studies is that mergers and acquisitions are profitable for acquired company’s shareholders but the wealth impacts on the acquirer company’s shareholders is however ambiguous. In addition the wealth effects seems to be more positive during the short-term but the positive effects seem to vanish after longer examined period. Previous studies have mainly concentrated on US and UK markets and there are not many studies conducted with Finnish data. The purpose of this study is to find out whether the mergers and acquisitions are profitable transactions for the shareholders of the acquiring company. Analysis is conducted for both, short- and long- terms and in addition the recent financial crisis is taken into account. Short-term results are examined with general event study methodology and the statistical significance of abnormal returns is tested with t-test. Long-term results are examined with wealth relative method and finally the volatility adjusted mean components from wealth relatives are tested with t-test. General event study methodology is appropriate method for short-term studies but in order to avoid the problems which arise from long-term event studies, this research paper exploits the wealth relative method for long-term period analyze. The results suggest that in the short-term Finnish companies’ M&A transactions have even positive impact on shareholders’ wealth. When the examined period is extended the wealth impact decrease and finally the M&A transactions seem to generate negative returns. In addition the results suggest slight improvement in profitability during the crisis period but any of the difference was not statistically significant.
Keywords: mergers and acquisitions; wealth relative; event study; financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|